Climate adaptation and conservation agriculture among Peruvian farmers - Tambet, Heleene; Stopnitzky, Yaniv (Agricultural and Applied Economics Association, 2021)
Peruvian agriculture will likely experience serious economic impacts of climate change, with changing rainfall and temperature patterns forcing farmers to confront abnormal climate conditions. In this context we study the impact of climate shocks on the agricultural practices of farmers who grow two main staples: maize and potato. We focus on four types of agricultural techniques: (a) those that reduce soil degradation, (b) those that conserve water, (c) the application of inorganic fertilizer, and (d) the application of pesticides and herbicides. We combine three rounds of cross‐sectional data from the Peru National Agricultural Survey with long‐term climate data to construct georeferenced shocks of abnormal rainfall levels and variation. Our empirical strategy controls for time‐invariant characteristics of small localities, secular time trends, and farmer and farm characteristics to estimate how shocks affect farmers' choices in subsequent growing cycles. Our findings show that: (a) farmers reduce soil conservation practices after one year of high rainfall, but multiple years of low rainfall increase adoption significantly; (b) the rate of pesticide use increases by eight percentage points following a drought year but is insensitive to multiple shock years; (c) water conservation measures are used less after high precipitation or when volatility was unusually low, and multiple years of insufficient rain tend to enhance this response; and (d) fertilizer use is less sensitive than other outcomes to weather fluctuations. These findings suggest that understanding how responsive farmers' practices are to weather shocks can inform policy design and help mitigate risks from changing weather patterns.